Environmentally Friendly Mesoporous Nanocomposite Prepared from Al-Dross Waste with Remarkable Adsorption Ability for Toxic Anionic Dye - Inas A. Ahmed; Najlaa S. Al-Radadi; H. S. Hussein; Ahmed H. Ragab (Journal of Chemistry)
In this work, a mesoporous nanocomposite composed of nanogibbsite (α-Al(OH)3) and nanosilica was prepared. Gibbsite nanoparticles (GNPs) with a crystal size of ≈38 nm were prepared from Al-dross industrial waste products in an acidic environment at 100°C. Nanosilica (NS) with a crystal size of ≈13 nm was prepared from sodium silicate using dilute hydrochloric acid. The deposition of nanosilica onto gibbsite particles was investigated. The mesoporous silica-gibbsite (NSG) nanocomposite was examined by evaluating its ability to adsorb the toxic anionic dye Eriochrome black T (EBT) from aqueous solution. The compositional and morphological properties of NSG nanocomposites were studied by means of the FTIR spectroscopy, X-ray fluorescence (XRF), XRD, SEM, and TEM techniques. The effect of dye concentration, pH, adsorbent dose, contact time, and temperature was investigated. The sorption models, the isotherms, and the thermodynamic parameters ΔHo, ΔGo, and ΔSo were evaluated. The N2 adsorption-desorption isotherms revealed that mixing the two prepared materials (NS and GNPs) to form the NSG nanocomposite resulted in good properties (a surface area of 62.34 m2·g−1, a pore radius of 22.717 nm, and a pore volume of 0.7081 cm3·g−1). The results show that the prepared NSG nanocomposite has a remarkable ability to adsorb toxic anionic dyes.